A novel image encryption algorithm based on dynamic S-boxes constructed by chaos - Wang, Xingyuan; Wang, Qian (Nonlinear dynamics, 2014)
In this manuscript, an image encryption based on dynamic S-boxes is presented, in which the S-boxes are constructed by chaotic systems. An external 256-bit key and the last pixel of plain image are used to generate the parameters and initial states of the chaotic systems for the first S-box. The plain image is divided into groups in which the pixels are substituted by S-boxes and in order to smash the correlation of adjacent pixels the image is grouped in four directions. After encrypting previous group, the initial states of chaotic systems are altered by encrypted image pixels and the S-box for the next group is generated. This algorithm scheme can make it resist differential attacks and chosen plain-text attacks. Moreover, because in the all process we only need to construct less than 50 S-boxes, the progress time is reduced. Superiority in speed and security is analyzed by applying the algorithm on 256-grey images.